Pengaruh Self Congruity, Perceived Price, Brand Trust, dan Customer Engagement terhadap Willingness to Continue and Subscribe pada Disney Plus Hotstar - Abrari, Fuad; Sukresna, I Made (Universitas Batanghari Jambi, 2024)
The advancement of online streaming media and the growing interest of the Indonesian population in Video on Demand (VoD) applications have paralleled the development of the internet in Indonesia. The presence of various video streaming platforms with local, regional, and global reach operating in Indonesia has generated significant dynamics in the digital entertainment industry. This phenomenon has rapidly transformed the landscape, fostering the adoption of technology and altering consumer behavior patterns in accessing entertainment content. This research is aimed at uncovering the relationship between self-congruity and perceived price through various variables such as customer engagement and brand trust, which have implications on willingness to continue and subscribe. The study employs a quantitative research method or survey approach. Sample selection is conducted through non-probability sampling using purposive sampling techniques, with a total sample of 146 respondents who are customers of Disney+ Hotstar Indonesia. Data analysis is performed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach. The findings of the research reveal positive and significant influences, namely, self-congruity on brand trust, self-congruity on customer engagement, perceived price on customer engagement, brand trust on willingness to continue and subscribe, and customer engagement on willingness to continue and subscribe.